Ground water pollution due to aquaculture in east coast region of Nellore district, Andhrapradesh, India - Ramesh Reddy Putheti; R N Okigbo; Madhusoodan sai Advanapu; Radha Leburu (Advances in Aquaculture and Fisheries Management, 2020)
Ground water quality parameters were studied for pollution due to aquaculture in the east coast region of district Andhrapradesh, India. Over a period of two years, 46 groundwater samples were collected for analyses. The results showed that the alkalinity ranged from 120 - 482 mg/L, and pH ranged from 7.1 to 8.6. The chloride concentration ranged from 65 – 4950 mg/L, Dissolved Oxygen (DO) was 2 to 8.4 mg/L, and Biochemical Oxygen Demand was 3 to 23 mg/L. Conductivity ranged from 68 to 8200 umho/cm. Approximately 86 % of water samples exceed the international chloride standards for drinking water (200 – 250 mg/L). The Dissolved Oxygen (DO) concentration was within the acceptable standards of 6 mg/L. The DO concentration of the ground water satisfied the DO requirement for aquaculture. However, open well number 12 has less (3.1 mg/ml), potentially indicating contamination from aquaculture farm effluents. Low concentrations of Dissolved Oxygen in nearby well water provided further evidence that these wells are contaminated with biodegradable organic compounds. The effect of aqua farms on the ground water quality was discussed in line with public health standard